2021
DOI: 10.1021/acsomega.1c02049
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Multiphase Mechanical Properties of the Longmaxi Formation Shale Using Nanoindentation Tests

Abstract: Mechanical properties are some of the most important parameters for understanding well drilling and hydraulic fracturing designs in unconventional reservoir development. As an effective tool, nanoindentation has been used to determine the mechanical properties of rocks at the nanoscale. In this study, the Longmaxi Formation shale samples from the Yibin area of China were collected and analyzed to obtain the multiphase mechanical properties. The mineral compositions and organic geochemistry of the shale samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“… 13 17 This technique uses only small sample volumes (cuttings are acceptable) and can quickly generate large amounts of mechanical data. It therefore greatly aids the analysis of the micromechanical properties of shale; examples include the calculation of the mechanical parameters of individual phases in shales, such as minerals 16 19 and organic matter, 14 , 15 , 20 23 the relationships between mineralogy and bulk mechanics of shale, 14 , 15 , 24 the elastic anisotropy of shale, 17 , 25 , 26 and the methods for the prediction of the macromechanical properties of shale. 23 , 26 , 27 Besides, nanoindentation can also be used to study shale creep.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 17 This technique uses only small sample volumes (cuttings are acceptable) and can quickly generate large amounts of mechanical data. It therefore greatly aids the analysis of the micromechanical properties of shale; examples include the calculation of the mechanical parameters of individual phases in shales, such as minerals 16 19 and organic matter, 14 , 15 , 20 23 the relationships between mineralogy and bulk mechanics of shale, 14 , 15 , 24 the elastic anisotropy of shale, 17 , 25 , 26 and the methods for the prediction of the macromechanical properties of shale. 23 , 26 , 27 Besides, nanoindentation can also be used to study shale creep.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional uniaxial/triaxial compression tests can reveal the macroscopic mechanical properties and creep behavior of shale. However, these tests are generally time-consuming and require high-quality samples comprising a large volume free from fracture, which is generally difficult to obtain in field sampling. Therefore, nanoindentation has been introduced as an alternative technique to characterize the mechanical properties of shale. This technique uses only small sample volumes (cuttings are acceptable) and can quickly generate large amounts of mechanical data. It therefore greatly aids the analysis of the micromechanical properties of shale; examples include the calculation of the mechanical parameters of individual phases in shales, such as minerals and organic matter, ,, the relationships between mineralogy and bulk mechanics of shale, ,, the elastic anisotropy of shale, ,, and the methods for the prediction of the macromechanical properties of shale. ,, Besides, nanoindentation can also be used to study shale creep . Wick reported that nanoindentation gave results that were comparable with those of conventional uniaxial compression testing for creep behavior; thus, they believed that nanoindentation measurements were reliable in determining the creep behavior of shales .…”
Section: Introductionmentioning
confidence: 99%
“…The total organic carbon content varies from 2 to 4%, with a high proportion of micropores . In addition, the samples are mainly composed of quartz and clay minerals (about 70%), presenting brittle and hard lithology and strong heterogeneity …”
Section: Methodsmentioning
confidence: 99%
“…33 In addition, the samples are mainly composed of quartz and clay minerals (about 70%), presenting brittle and hard lithology and strong heterogeneity. 34 Shale samples were taken from massive carbon shale and further crushed in the laboratory. The broken shales were classified according to the particle size.…”
Section: Methodsmentioning
confidence: 99%
“…The nanoindentation technique has been extensively adopted for probing the mechanical properties of materials at the nanoscale, such as contact stiffness, Young's modulus, and hardness. Nanoindentation hardness and modulus of KNN-based ceramics and PZT-based ceramics (Pb 0.5 Sr 0.05 Zr 0.54 Ti 0.46 O 3 -1 wt% Sb 2 O 3 , abbreviated as PSZT) were calculated using Oliver and Pharr method by fitting the unloading curve to the power-law relation 36 :…”
Section: Nanoindentation Hardness and Young's Modulusmentioning
confidence: 99%